Investigating Attitudes, Motivations and Key Influencers for COVID-19 Vaccination Uptake among Late Adopters in Urban Zimbabwe - Azure Tariro Makadzange; Patricia Gundidza; Charles Lau; Janan Dietrich; Nellie Myburgh; Nyasha Elose; Wilmot James; Lawrence Stanberry; Chiratidzo Ndhlovu (Vaccines, 2023)
The rapid development of vaccines in response to the COVID-19 pandemic has provided an effective tool for the management of COVID-19. However, in many African countries there has been a poor uptake of COVID-19 vaccines with only 32.5% first vaccine dose coverage compared to the WHO global target of 70%. As vaccine access improves, one of the important drivers of low uptake has been vaccine hesitancy, driven by levels of confidence, convenience, and complacency. Between 4 January–11 February 2022, we conducted a survey of vaccine late adopters to assess factors that influenced adults in Harare, Zimbabwe to present for their first COVID-19 vaccine dose almost 12 months after the vaccination program began. Of the 1016 adults enrolled, 50% were female and 12.4% had HIV co-infection. Binary logistic regression models were developed to understand factors associated with vaccine confidence. Women were more likely to have negative views about the COVID-19 vaccine compared to men (OR 1.51 (95%CI 1.16, 1.97, p = 0.002). Older adults (≥40 years) compared with youth (18–25 years) were more likely to have ‘major concerns’ about vaccines. When asked about their concerns, 602 (59.3%) considered immediate side effects as a major concern and 520 (52.1%) were concerned about long-term health effects. People living with HIV (PLWH) were more likely to perceive vaccines as safe (OR 1.71 (95%CI: 1.07, 2.74, p = 0.025) and effective (1.68 (95%CI: 1.07, 2.64, p = 0.026). Internet users were less likely to perceive vaccines as safe (OR 0.72 (95% CI: 0.55, 0.95, p = 0.021) compared to non-Internet users; and social media was a more likely source of information for youth and those with higher education. Family members were the primary key influencers for 560 (55.2%) participants. The most important reason for receiving the COVID-19 vaccine for 715 (70.4%) participants was the protection of individual health. Improving vaccine coverage will need targeted communication strategies that address negative perceptions of vaccines and associated safety and effectiveness concerns. Leveraging normative behavior as a social motivator for vaccination will be important, as close social networks are key influences of vaccination.